Fibrinogen Bβ polymorphisms do not directly contribute to an altered in vitro clot structure in humans - Maghzal, Ghassan J.; Brennan, Stephen O.; George, Peter M. (Thrombosis and Haemostasis, 2003)
Fibrinogen Bβ polymorphisms, such as the -455 G/A and the Arg448Lys amino acid substitution, have been shown to increase the risk of atherothrombotic disease. Although these polymorphisms are related to fibrinogen concentrations, their effect on fibrin clot structure has not been extensively studied. We examined the frequency of the fibrinogen Bβ -455 G/A polymorphism in a group of myocardial infarction (MI) patients. There was no association between this polymorphism and MI. However, we found that patients homozygous for the rare -455 A allele had a higher average age at first MI. A similar result was found for individuals homozygous for the Bβ 448 Lys allele who also had a higher age at first MI.We subsequently studied the clotting properties of purified Arg448 and Lys448 fibrinogens in vitro and found that these fibrinogens did not significantly differ in their polymerisation, fibrinolysis kinetics or in their clot permeation properties. Mass spectrometry analysis of endoproteinase Asp-N digests of Bβ chains revealed that the Lys448 and the Arg448 chains were expressed in approximately equal proportions in a heterozygote Arg448Lys individual. Our results demonstrate that the fibrinogen Bβ –455 G/A polymorphism is not associated with myocardial infarction and furthermore the closely linked Bβ Arg448Lys protein coding variation does not have an influence on the function nor the structure of the protein in a purified system.
Keywords: Atherosclerosis; fibrinogen / fibrin; polymorphisms; clot structure; expression